2012
DOI: 10.1039/c2jm34603f
|View full text |Cite
|
Sign up to set email alerts
|

Phase evolution, phase transition, and microwave dielectric properties of scheelite structured xBi(Fe1/3Mo2/3)O4–(1−x)BiVO4 (0.0 ≤ x ≤ 1.0) low temperature firing ceramics

Abstract: In the present work, the xBi(Fe 1/3 Mo 2/3 )O 4 -(1Àx)BiVO 4 (0.0 # x # 1.0) ceramics were prepared via the solid state reaction method. All the ceramics can be densified at low sintering temperatures around 820 C. At room temperature, the BiVO 4 type scheelite monoclinic solid solution was formed in ceramic samples with a composition of x # 0.10. When x lies between 0.1 and 0.7, a BiVO 4 scheelite tetragonal phase is formed at room temperature. In the range 0.7 # x < 0.9, the ceramic samples were found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
51
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 29 publications
4
51
2
Order By: Relevance
“…In our previous work, [3,[8][9][10][11][12] a series of ultralow-temperature-firing microwave dielectric ceramics with low (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), medium , and high k values (Ͼ40) have been explored. Among them, Bi 2 Mo 2 O 9 seems to be very promising owing to its ultralow sintering temperature of ca.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, [3,[8][9][10][11][12] a series of ultralow-temperature-firing microwave dielectric ceramics with low (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), medium , and high k values (Ͼ40) have been explored. Among them, Bi 2 Mo 2 O 9 seems to be very promising owing to its ultralow sintering temperature of ca.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Many classic microwave dielectric ceramics based on ABO3 perovskite structure have been explored and the relation between structure-property has been extensively studied. 5,6 Recently, many complex oxides with classic ABO4 type, such as scheelite (CaMoO4, BiVO4), 7,8 Fergusonite (LaNbO4, NdNbO4), 9 stibiotantalite (BiNbO4, BiTaO4), 10,11 wolframite (ZnWO4, MgWO4), 12 zircon (CeVO4) 13 and rutile ((Zn,Nb)TiO4, (Cu,Nb)TiO4) 14 lattice. In the present work, a comprehensive study on the phase assemblage and evolution in (Bi,Y)VO4 system was performed with the zircon-type solid solution region and its associated sintering behavior, microstructure and microwave dielectric properties were studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, research on both sites' simultaneous replacement was an effective way to overcome the shortcomings of those separate substitution. Also due to the fact that many other studies has reported the positive effects of single Bi substituting (0.05 B x) at Nd site on the system, goals of the investigation were to study the impact of substitution in Al-replaced Ba 3.75 Nd 9.5 Ti 18 0 54 (0.05 B x B 0.2) ceramic on microwave dielectric properties and to find a proper x value range that would conduct good dielectric properties [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%